Regional Language Revitalization Strategies for Safeguarding Intangible Cultural Heritage - Suci Nurmala; Nining Widia Sari; Bernard C. Perley (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Regional languages constitute one of the most important forms of intangible cultural heritage because they preserve indigenous knowledge, local wisdom, traditional values, oral traditions, and collective cultural identities. Nevertheless, globalization, urbanization, technological transformation, and the dominance of national and international languages have accelerated language shift across many multilingual societies, particularly in Indonesia. This article aims to analyze comprehensive strategies for regional language revitalization through the integration of educational institutions, cultural policies, community participation, and digital innovation. This study employed a qualitative library research design using a systematic literature review of recent international and national publications related to language revitalization, language preservation, and intangible cultural heritage. Thirty scholarly publications published between 2012 and 2026 were critically analyzed using thematic content analysis. The findings reveal four interconnected strategic dimensions that significantly contribute to successful language revitalization: educational transformation, community empowerment, policy intervention, and technology-based innovation. Educational institutions strengthen intergenerational language transmission through curriculum integration, while community participation maintains authentic language practices within cultural contexts. Government policies create sustainable institutional support, whereas digital technologies expand language use among younger generations through multimedia platforms and digital documentation. The study proposes an integrated revitalization framework emphasizing collaboration among governments, educational institutions, local communities, and digital stakeholders. The framework contributes to sustainable language maintenance while reinforcing regional cultural identity in the era of globalization.